LA CREATION DU PARC DE LA LOMAMI ET LA DELOCALISATION DE LA POPULATION RIVERAINE : ENJEUX, DEFIS ET PERSPECTIVES - MWAIKENGA, Marie BWASA; RAMAZANI, Lucien MUSAMBAY; GLORIA, Ruphin ZONGODIO (IJRDO - Journal of Social Science and Humanities Research, 2022)
The creation of the Lomami National Park has been the basis of its local population, despite the fact taht it has the right to live in its forest and enjoy all its related rights. It is shown in this study that this relocation was made without respecting the regulations in this area. Thus, this study aims to :Demonstrate how the Democratic Republic of Congo can reconcile the protection of ecosystems in the Lomami National Park and the protection of human rights ;Identify the consequences of the relocation of the local popultion following the creation of the Lomami National Park.To achieve the objectives assigned to this study and verify the hypotheses it proposes, recourse was made to the legal method. This method was combined with the systemic appoach and documentary and interview techniques.